Reasons why doctors choose or reject careers in general practice: national surveys. - Lambert, T; Goldacre, R; Smith, F; Goldacre, M (2012)
BACKGROUND: Less than one-third of newly qualified doctors in the UK want a career in general practice. The English Department of Health expects that half of all newly qualified doctors will become GPs. AIM: To report on the reasons why doctors choose or reject careers in general practice, comparing intending GPs with doctors who chose hospital careers. DESIGN AND SETTING: Questionnaire surveys in all UK medical graduates in selected qualification years. METHOD: Questions about specialty career intentions and motivations, put to the qualifiers of 1993, 1996, 1999, 2000, 2002, 2005, 2008, and 2009, 1 year after qualification, and at longer time intervals thereafter. RESULTS: 'Enthusiasm for and commitment to the specialty' was a very important determinant of choice for intending doctors, regardless of chosen specialty. 'Hours and working conditions' were a strong influence for intending GPs (cited as having had 'a great deal' of influence by 75% of intending GPs in the first year after qualification), much more so than for doctors who wanted a hospital career (cited by 30%). Relatively few doctors had actually considered general practice seriously but then rejected it; 78% of the doctors who rejected general practice gave 'job content' as their reason, compared with 32% of doctors who rejected other specialties. CONCLUSION: The shortfall of doctors wanting a career in general practice is not accounted for by doctors considering and rejecting it. Many do not consider it at all. There are very distinctive factors that influence choice for, and rejection of, general practice.